2007
DOI: 10.1016/j.appet.2006.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbohydrate diets cause obesity, low-carbohydrate diets reverse obesity: A metabolic mechanism resolving the paradox

Abstract: High-fat diets produce obesity in part because, per calorie, glucose produces greater post-prandial thermogenesis than lipids, an effect probably mediated by glucose-sensing neurons. A very low carbohydrate/high-fat/high-protein Atkins-type diet produces obesity but is marginally ketogenic in mice. In contrast, high-sucrose/low-fat diets, and very low carbohydrate/high-fat/low-protein (antiepileptic) ketogenic diets reverse diet-induced obesity independent of caloric intake. We propose that a non-ketogenic hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 41 publications
5
13
1
1
Order By: Relevance
“…However, when surgery was performed on these mice and they lost weight as is usual after surgery, mice on the high-protein diet did exhibit higher levels of blood 3-beta-hydroxybutyric acid, consistent with the ketogenic effects of the high-protein, low-carbohydrate diet during caloric restriction [20]. Under standard ad lib fed conditions, in contrast to the ketogenic diet, rather than reduce body weight, this diet promoted weight gain and other obese phenotypes just as do standard high-fat "Western" diets in mice [25]. Furthermore, despite low carbohydrate, blood glucose was not significantly reduced, and in fact trended to increase as the mice gained weight.…”
Section: Low-carbohydrate Diets In Animal Models Of Obesity and Diabetessupporting
confidence: 61%
See 1 more Smart Citation
“…However, when surgery was performed on these mice and they lost weight as is usual after surgery, mice on the high-protein diet did exhibit higher levels of blood 3-beta-hydroxybutyric acid, consistent with the ketogenic effects of the high-protein, low-carbohydrate diet during caloric restriction [20]. Under standard ad lib fed conditions, in contrast to the ketogenic diet, rather than reduce body weight, this diet promoted weight gain and other obese phenotypes just as do standard high-fat "Western" diets in mice [25]. Furthermore, despite low carbohydrate, blood glucose was not significantly reduced, and in fact trended to increase as the mice gained weight.…”
Section: Low-carbohydrate Diets In Animal Models Of Obesity and Diabetessupporting
confidence: 61%
“…Nevertheless the diet reduced blood glucose, associated with an induction of FGF21 [24], consistent with the studies of Phinney et al, who demonstrated reduced blood glucose and insulin, and reduced whole-body glucose utilization, without weight loss. Our laboratory carried out a similar study using the same Bioserve diet and got essentially identical results [25], although our analysis was not as extensive as that of Kennedy et al [23]. However, we carried out an additional study.…”
Section: Low-carbohydrate Diets In Animal Models Of Obesity and Diabetesmentioning
confidence: 67%
“…Although the mechanisms of ketogenesis might differ between humans and rats, our findings question whether people performing Atkins'-style diets being rather moderate in fat content actually reach a constant state of ketosis. Similarly, it has recently been reported that a very low-carbohydrate/high-fat/ high-protein Atkins-type diet is only marginally ketogenic in mice (34). Regardless of the occurrence of diet-induced ketosis in humans, one has to ask if the energy loss via ketone bodies in urine can quantitatively contribute significantly to the overall energy balance.…”
Section: E73 Ketosis Induction With Low-carbohydrate/high-fat Diets Imentioning
confidence: 99%
“…The determination and quantification of sugars has a great significance in many fields such as food industries, medical applications, wastewater treatment, and many others [1][2][3]. The development of sensors and/or biosensors presents an advantageous alternative for ''in loco" measurements, however some aspects including durability, limits of detection and selectivity require further improvement.…”
Section: Introductionmentioning
confidence: 99%